2016
DOI: 10.1063/1.4944531
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microwave-to-terahertz absorption in graphene

Abstract: Fresnel equations predict that an ultrathin free standing conductive film, thousands times thinner than skin depth, is capable to absorb up to 50% of incident electromagnetic radiations. In the microwave range, the same holds true for a free standing graphene sheet. We demonstrate theoretically and prove experimentally that microwave absorptance of graphene can be enhanced considerably by depositing graphene on a dielectric substrate. On the experimental side, we obtain 80% and 65% absorptance at 30 GHz and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 12 publications
0
60
0
Order By: Relevance
“…, maximal absorptance in graphene corresponds to some optimal value of the effective sheet conductance. Such an optimal value can be reached by combining several graphene layers in sandwich structure . Fine‐tuning to the exact value of optimal conductance can be fulfilled by applying strain to one of the layers.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…, maximal absorptance in graphene corresponds to some optimal value of the effective sheet conductance. Such an optimal value can be reached by combining several graphene layers in sandwich structure . Fine‐tuning to the exact value of optimal conductance can be fulfilled by applying strain to one of the layers.…”
Section: Theorymentioning
confidence: 99%
“…Recently, we have demonstrated that free standing multilayered structures consisting of alternating graphene monolayers and submicron‐thin polymer (PMMA) slabs are capable to absorb up to 50% of the radiation, depending on the number of graphene sheets, thus providing an efficient microwave shielding. According to admittance‐matching conditions, in case of using a proper dielectric substrate being 1/4 of wavelength thick, or metamaterials‐like type, it is possible to reach almost perfect absorption. The concept of EM components relying on graphene high absorption ability in microwave‐THz frequency range has been proposed in our recent work: high performance of graphene in shields, filters, polarizers, operating at the GHz and THz frequencies has also been recently demonstrated …”
Section: Introductionmentioning
confidence: 99%
“…Finally, a comparison of our results with known results for other metasurface absorbers is in order. Batrakov et al [22] fabricated a cascade of five graphene layers to obtain A = 0.65 at ∼ 1 THz with ∼ 0.2-THz full-widthat-half-maximum (FWHM) bandwidth. In contrast, our optimal device can have, for example, A ≥ 0.95 for 3.5 ± 0.75 THz (Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that nano‐thin conductive carbon and graphene films could be highly absorptive ability at certain thickness which is inversely proportional to their conductivity . The idea of this communication is to present a tunable EMI shielding layer based on fluorinated graphene.…”
Section: Introductionmentioning
confidence: 99%